(untitled) (Journal of Scientific Research, 2014)
Cu1-xMgxFe2O4 ferrites with (x = 0.2, 0.4, 0.6, 0.8 and 1.0) has been synthesized by double sintering ceramic technique at 11500C for 2hr and investigated for their structure, microstructure, complex permeability behaviour, DC and AC resistivity, dielectric constant measurements. X-ray analysis indicated the formation of single-phase cubic spinel structure for all samples and the lattice parameter was found to decrease with increasing Mg content. Grain size was found to decrease from 34.36 to 4.16 mm with the increase of Mg contents. The real part of initial permeability (??) remained constant up to certain lower range of frequency after it decreased slightly to lower value of permeability at which imaginary part of permeability (?²) showed a maximum value. The decrease of ?? is observed with the increase of Mg content which is attributed to a decrease of grain size. DC electrical resistivity and dielectric constant decreased with increasing Mg content and AC resistivity decreased with increasing frequency, exhibiting normal ferrimagnetic behaviour. The observed variation of electrical and dielectric properties has been explained on the basis of the electronic hopping frequency between Fe2+ and Fe3+ ions in present samples. Keywords: Ferrites; XRD; Micrographs; Complex permeability; DC resistivity. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.17351 J. Sci. Res. 6 (2), 205-215 (2014)